Analisis Faktor-Faktor yang Mempengaruhi Kecenderungan Fraud Akuntansi Di Pemerintahan Desa Se-Kecamatan Mojoagung Kabupaten Jombang - Mochamad Thorik; Munari , (JRAK: Journal of Accounting Research and Computerized Accounting, 2022)
Fraud is one of the big problems in accounting. Corruption has to do with fraud. In 2015 the central government allocated a considerable village-level budget to the village head for village-level development, but in reality there are still many cases of village governments misusing village funds. Therefore, the purpose of the study was to determine whether organizational culture, effectiveness of internal controls, adherence to accounting rules and compensation conformity negatively influence accounting fraud tendencies. Quantitative is this type of research. The primary data used in this research was distributed through an online questionnaire filled out by 54 respondents, consisting of the Village Head, Village Secretary, and Head of The Village Government Finance Section of Mojoagung District of Jombang Regency. Multiple linear regression analysis is used to analyze the data in this research. The results of this study showed that organizational culture and adherence to accounting rules had an insignificant positive influence, while the effectiveness of internal controls had a significant negative influence and the suitability of compensation had no significant negative influence on accounting fraud tendencies. Keywords: Culture; Effectiveness; Obedience; Conformity; Fraud